Reality bytes. Hybrid inter-faces, hybrid selves - Lopez, Mario (Acta Orientalia Vilnensia, 2008)
Kyoto UniversityOver the past 20 years, computer games have become a very integral part of consumptive practices, acting as a guide to mediate multiple selves. This sets the context for this paper, a philosophical inquiry into the creation and mediation of ‘selves’ through the consumption of Japanese computer games, taking a detailed look at some of the symbolic and semiotic structures that permeate game structures. Games placed in the realm of human creativity and normative freedoms are as argued in this paper, a subtle form of the Deleuzian concept of assemblage.This paper argues that the ‘self’ as seen through computer games manifest multiple ‘selves’ that highlight the fluidity of identities which are being fabricated, disseminated and transmitted from Japan. Through an analysis of a number of Japanese games popular in Japan and actively consumed abroad, this paper examines an underlying grammar that transcribes the self and how social relations are reworked through technological enquiry. This paper further highlights how computer-dominated social practices that have heavily flowed from Japan have introduced very specific ontological ways of seeing the world to a whole generation of games players residing in other geographical spheres.